Efficacy and safety of extracorporeal shock wave therapy for upper limb tendonitis: a systematic review and meta-analysis of randomized controlled trials - Xiong, Yongqing; Wen, Tianshan; Jin, Songzhi; Lin, Ling; Shao, Qianer; Peng, Yue; Zheng, Qining; Li, Wei (Frontiers in Medicine, 2024)
Objective: This study synthesised the highest level of evidence to analyse the effectiveness and safety of using extracorporeal shock wave therapy (ESWT) to treat upper limb tendonitis, which was unknown.We conducted a systematic review and meta-analysis of 18 randomized controlled trials (RCTs) in PubMed, Embase, Web of Science, Medline, and the Cochrane Library.Methods: Two researchers performed the screening, data extraction, literature quality assessment, and heterogeneity analysis of the searched RCTs.The main types of morbidity included rotator cuff tendonitis, lateral epicondylitis, finger tendonitis, and long bicipital tendonitis. The results of the metaanalysis showed that ESWT was effective in relieving pain in all four types of tendonitis. In addition, ESWT was more effective in relieving pain in patients with upper limb tendonitis than placebo at the three-and six-month follow-ups, especially with radial ESWT (RESWT). Data analysis of the forest plot showed that the 2 experimental group with ESWT as an intervention had a significant improvement in function in patients with rotator cuff tendonitis at the three-month follow-up.However, subgroup analysis showed that low-energy ESWT was effective in improving function in patients with calcified and non-calcified rotator cuff tendonitis, whereas it was not effective in relieving pain.ESWT can effectively improve the functional activity in patients with rotator cuff tendonitis and may produce positive analgesic effects in patients with upper limb tendonitis. The incidence of adverse effects is low.